Using Marketing Mix Strategies to Influence Customer Patronage in an Indigenous Restaurant - Oyenuga Michael Oyedele; Labiyi Opeyemi (Britain International for Academic Research (BIAR) Publisher, 2024)
Organisations will always strive to ensure that customers come back for repeat purchases and this cannot be achieved if they were not satisfied in the first place. Ensuring customer satisfaction is a prerequisite to customer patronage yet the latter cannot be achieved if there were no conscious efforts by the organization to put in place a blend of strategies that can be effectively measured. This research was carried out to examine the effect of marketing mix strategies on customer patronage in an indigenous restaurant in Abuja, Nigeria. A cross-sectional descriptive study was adopted as the research design. The participants were customers of a restaurant in Abuja, with sample data of 353 collected through a questionnaire. The link between the dependent and independent variables was determined using regression analysis, and data analysis was conducted using the Statistical Package for Social Sciences (SPSS 24). The results of the regression model show that price has a positive but not significant effect on customer patronage while physical facilities are also established to have a significant impact on customer patronage at Amala Spot, Abuja. This study, therefore, concluded and recommended that restaurateurs, especially indigenous ones must provide customers with logicality of perceived price. One management approach is to offer the appropriate quality of physical environment to customers.